Análisis de los factores que limitan el desarrollo de las pequeñas empresas de la ciudad de Loja. - Benitez Rivera., Marjorie Briggette (2024)
Small businesses, despite their size, play a fundamental role in the economic environment in Loja city. They represent an important part of the economy and contribute to the generation of employment; however, these small companies are hindered by various limiting factors, both internal and external. The general objective of the research was to analyze the factors that limit the development of small enterprises in the city of Loja, and the specific objectives were to identify the internal factors that limit their growth and to identify the external factors that limit their development, as well as to propose business strategies to overcome these limitations. For this study we used the methodology of convenience, the deductive method with quantitative approach and descriptive type of research, for data collection a survey was conducted to small businesses, a simple random sampling was applied. In addition, a SWOT analysis was carried out as a tool for diagnosing and formulating business strategies. Internal factors (business management and specialized talent) are considered by some small enterprises as an obstacle to their growth. External factors (difficulty in accessing financial resources and high interest rates) are seen as obstacles to their development. In addition, it was determined that the adoption of new technologies, competitiveness, government policies and the requirements for their operation can generate high costs and complicate the development of small businesses and that most companies comply with government policies, but some entrepreneurs see them as limiting due to costs and taxes.